Apocalipsis XX di Sara de Ibáñez (Altre Modernità, 2013)
Rewriting the text of Saint John, Sara de Ibáñez uses a kind of style innovative and away from schools and trends in vogue: is thus able able to evoke the tragic experiences of the twentieth century, but the date of publication of the book (1970) reveals that it advances in themes and forms the concrete apocalypse lived by Uruguay and Latin America in the seventies.However, far from political themes and motifs, Sara de Ibáñez is able to express the absolute horror of contemporary tragedies and to propose a poetic reflection of great quality. This article suggests a rediscovery of this twentieth-century poetic voice, unjustly forgotten, through her 'apocalyptic' text.